Analisis Kelayakan Pemberian Pembiayaan Multiguna Dalam Meminimalisir Resiko Pembiayaan Pada Bank Sumut Syariah Cabang Medan Katamso - Ahmad Fauzan Soleh; Waizul Qarni (CEMERLANG : Jurnal Manajemen dan Ekonomi Bisnis, 2023)
Multipurpose financing is comprehensive financing where this financing is very much needed by the community where the financing is a consumer financing facility based on a Murabahah contract or multi-service ijarah contract for the purpose of purchasing halal goods and services obtained according to sharia, usually such as building materials, for house renovations, motorbike ownership. , education costs, and home equipment. This research aims to find out a procedure for having multipurpose IB Muamalat financing and to find out the steps taken to minimize the risk of customers defaulting on Muamalat financing. This research aims to describe several things, which include procedures for providing Multipurpose financing, problems in providing Multipurpose financing, and solutions to problems that occur in Multipurpose financing (PMG) at PT. Bank SUMUT Syariah Medan Katamso Branch Office. This research uses a descriptive method. The data source used is secondary data. The type of data used is qualitative data with the documentation used is a flowchart of procedures for granting Multipurpose Credit, and direct interviews by holding questions and answers to the head of the marketing division at PT. Bank SUMUT Syariah Katamso Branch Office. Based on the results of the analysis from this research, it can be seen that the procedure for providing Multipurpose Financing to PT. Bank SUMUT Syariah Medan Katamso branch office goes through several stages that have been determined by the bank. The stages in granting Multipurpose Credit are application/submission of financing, investigation and analysis of financing, financing decisions, rejection and approval of financing, binding of collateral and realization of financing